Galangin, a natural flavonoid reduces mitochondrial oxidative damage in streptozotocin-induced diabetic rats - Amal A. Aloud; Chinnadurai Veeramani; Chandramohan Govindasamy; Mohammed A. Alsaif; Khalid S. Al-Numair (Taylor & Francis Group, 2018)
Objective: We designed this study to observe the effect of galangin on damaged mitochondria in the liver of diabetic rats. Methods: Male albino Wistar rats were made diabetic by injecting streptozotocin (STZ) intraperitoneally (40 mg kg−1 body weight (BW)). Galangin (8 mg kg−1 BW) or glibenclamide (600 µg kg−1 BW) was given orally daily once for 45 days to both healthy and diabetic rats. Results: Diabetic rats showed significant (P < 0.05) increase in liver mitochondrial oxidant [Thiobarbituric acid reactive substance (TBARS)] level and a significant decrease in enzymatic [superoxide dismutase (SOD), glutathione peroxidase (GPx)] and non-enzymatic (reduced glutathione (GSH)) antioxidant levels when compared with healthy rats. The mitochondrial enzymes isocitrate dehydrogenase (ICDH), alpha-ketoglutarate dehydrogenase (α-KGDH), succinate dehydrogenase (SDH) and malate dehydrogenase (MDH) and mitochondrial respiratory chain enzymes NADH-dehydrogenase and Cytochrome c-oxidase were decreased significantly (P < 0.05) in diabetic rats when compared with healthy rats. A natural flavonoid galangin administered to hyperglycemia-induced rats resulted in the following findings as compared to hyperglycemia-induced control rats: the oxidant levels decreased significantly (P < 0.05); the enzymatic and non-enzymatic antioxidant levels increased significantly (P < 0.05) and the function of mitochondrial enzymes and the mitochondrial respiratory chain enzymes increased significantly (P < 0.05). Conclusion: From the results, we conclude that galangin could maintain liver mitochondrial function in diabetic rats.